Training in Running Technique for Sprint Distances Taking into Account Individual Features - Abdujabbarovich, Chariev Ulugbek (International Journal on Orange Technologies, 2023)
The article discusses the technique of sprinting and ways to improve it, taking into account the individual characteristics of the athlete. The speed of overcoming the distance in sprinting depends both on the rational ratio of the length and frequency of running steps, and on the individual technique of the athlete.